2005
DOI: 10.1002/hipo.20123
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and nonhomologous end joining in excitotoxicity: Neuroprotective role of DNA-PKcs in kainic acid-induced seizures

Abstract: DNA repair plays a critical, but imprecisely defined role in excitotoxic injury and neuronal survival throughout adulthood. We utilized an excitotoxic injury model to compare the location and phenotype of degenerating neurons in mice (strain 129-C57BL) deficient in the catalytic subunit of the DNA-dependent protein kinase (DNA-PKcs), an enzyme required for nonhomologous end joining (NHEJ). Brains from untreated adult heterozygous and DNA-PKcs null mice displayed comparable cytoarchitecture and undetectable lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 92 publications
(99 reference statements)
6
39
0
Order By: Relevance
“…112 Neema et al suggested that p53-dependent neuronal death involves a drop in MTP, which reflects both a loss in the integrity of mitochondria and an increase in mitochondrial membrane permeability. 113 As described from an earlier study, the inner MTP decreases during apoptosis. Thus, the …”
Section: Pft-α Inhibits B-agnp-and F-agnpinduced P53-dependent Ros Prmentioning
confidence: 58%
“…112 Neema et al suggested that p53-dependent neuronal death involves a drop in MTP, which reflects both a loss in the integrity of mitochondria and an increase in mitochondrial membrane permeability. 113 As described from an earlier study, the inner MTP decreases during apoptosis. Thus, the …”
Section: Pft-α Inhibits B-agnp-and F-agnpinduced P53-dependent Ros Prmentioning
confidence: 58%
“…PFTa was also shown to protect against neuron degeneration induced by 6-Hydroxydopamine (Biswas et al 2005;Liang et al 2007), proteasome inhibitors (Nair et al 2006), and the herbicide paraquat (a suspected etiologic factor in the development of Parkinson's disease) (Yang and Tiffany-Castiglioni 2008). Moreover, PFTa inhibited glutamate-and kainite (an analog of glutamate)-induced p53-mediated neuronal death (Morrison et al 1996;Xiang et al 1998;Liu and Zhu 1999;Culmsee et al 2001;Neema et al 2005) and protected mouse synaptosomes against excitotoxic injuries (Gilman et al 2003).…”
Section: P53-driven Pathologiesmentioning
confidence: 99%
“…Moreover, neurons have low levels of antioxidant enzymes, thus particularly susceptible to the damaging and highly toxic effects of ROS (94). DNA-PK exerts a protec-tive function under different cell death conditions, including oxidative stress and excitotoxicity (71,73). Hence, it is possible that exposure to nonlethal oxidative injuries in the presence of A␤, a hallmark of AD pathology, elicits neuronal cell death by suppression of DNA-PK anti-apoptotic function, contributing to the neurodegenerative process.…”
Section: Discussionmentioning
confidence: 99%